CLINICO-EPIDEMIOLOGICAL PROFILE OF ORAL CANCER: A HOSPITAL BASED STUDY - Agrawal, Kapil H; Rajderkar, S S (Indian Journal of Community Health, 2012)
Background: India is heading towards various types of non-communicable diseases, which are also known as modern epidemics. Among these modern epidemics cancer is among the ten commonest cause of mortality in developing countries including India. Oral cancer is a major problem in India and accounts for 50-70% of all the cancers diagnosed. Ninety percent (90%) of oral cancers in South East Asia including India are linked to tobacco chewing and tobacco smoking. Research question: What is the profile of Oral cancer (Oral cavity) cases reported in the hospital? Objective: To study the clinico-epidemiological profile associated with Oral cancer cases. Methods: Study Design: Hospital based, Cross -sectional study. Settings: Shri Siddhivinayak Ganapati Cancer Hospital, Miraj, Maharashtra. Participants and Sample size: As it is a time bound study sample size comprised of all the confirmed cases of oral cancer reported in the hospital during the study period. The study was carried out from 1st March 2005 to 28th February 2006. Study variables included demographic factors, socioeconomic factors, enquiries regarding modifiable risk factors such as tobacco usage, alcohol consumption, site involved (within oral cavity), staging, histopathological examination, treatment modality used. Data entry and statistical analysis was done using Microsoft excel. Data presented in form of percentages and proportions. Results: Out of the total 160 cases, majority of the subjects were above 40 years age. 36 (22%) of subjects were young adults (below 40 years age). 125 (78%) subjects were male. Most of the subjects belonged to upper lower and lower middle socio-economic scale according to modified Kuppuswamy classification. It was observed that 139 (87%) cases consumed tobacco in all forms. Out of these, ninety cases consumed tobacco in chewable form. Tobacco was chewed mainly in the form of gutka. Only ten (10) female subjects chewed tobacco. No female subjects smoked. The most common site for oral cancer was tongue. Histopathologically 52 (32.5%) cases were well differentiated squamous cell carcinoma, 37 (23%) cases were moderately differentiated squamous cell carcinoma and 34 (21%) cases as poorly differentiated squamous cell carcinoma. 37 (23%) cases were diagnosed as Oral Verrucous Carcinoma (a rare variant of Oral Squamous Cell Carcinoma). 72% cases were in either stage II or stage III. Conclusions: The most common site for oral cancer was tongue and histopathologically majority of the cases were well differentiated squamous cell carcinoma presented in advanced stages of disease. We observed higher proportion of oral cancers among young patients (below 40 years). Proportion of Oral Verrucous Carcinoma (OVC) which is a rare variant of Oral Squamous Cell Carcinoma was also high in the study.